Project TIBOK Talaan at Iba't Ibang Opinyon Para sa Komprehensibong Sitwasyonal na Analisis - Araza, John Kloyd P.; Dela Cruz, Ron Louis D.C.; Guantia, Mary Gale R.; Martin, Ella Sheridy T.; Mateo, Eve Kathleen Marie E.; Medes, Jeandre Evan P.; Perfecto, Angeline M.; Pitallano, Jr., Noel M.; Punongbayan, Bea Mae V.; Ramoy, Maria Regina V.; Mistica, Myra S.; Claro, Paulyn Jean A.; et al. (Manila College of Public Health, University of the Philippines Manila, 2024)
Magallanes is a 4th class municipality that aims to serve as a focal point for agri-eco-tourism within the whole province of Cavite. It currently has 16 barangays under its jurisdiction, with a total population of 24, 528 as of 2023. There are 11 barangay health stations (BHS) and one Rural Health Unit (RHU) that are supervised by the Officer-in-Charge-Municipal Health Officer (OIC-MHO). In terms of the health system, a variety of health programs are being implemented in the Municipality of Magallanes, including the maternal and child care program, dental care program, and leprosy and rabies prevention and control program, among many others.

The need of the Magallanes RHU to identify and address pressing health issues was addressed through the conduct of a municipal-level situational analysis guided by the Mobilizing for Action through Planning and Partnership (MAPP) Framework. The group then described and analyzed the community's health status and health services by identifying the leading causes of morbidity and assessing their medicine and supplies, health facilities, and health programs.

The methodology included data review, identification of leading causes of morbidity, decision matrix creation, interview guides, actual interviews, and subsequent data analysis. In conclusion, the situational analysis revealed that hypertension is the leading cause of morbidity that should be prioritized in Magallanes.

Recommendations become evident for strengthening health systems, enhancing community engagement, and fostering improvements in the current municipal health programs. For health systems strengthening, expanding the Local Health Board (LHB) to improve leadership in the area is necessary. The establishment of technical working group is also deemed crucial. Results generated from the situational analysis conducted may also be a guide for the creation of evidence-based policies and programs. To enhance community engagement, it is recommended to undertake efforts such as conducting Barangay Ugnayan regularly to serve as a platform for the community to voice their concerns and for the government to convey information to the people effectively. The incorporation of health promotion and educational kiosks into all Barangay Health Stations (BHS) is also suggested. Recommendations are also put forth in light of examining potential improvements for health programs such as the Philippine Package of Essential Noncommunicable Disease Interventions (PhilPEN), vaccination efforts, and sanitation profiling. For PhilPEN, it is recommended to create a database of at-risk individuals who are unable to visit RHU. In addition to this, the observed shortage of such instruments during house-to-house visits is addressed. To facilitate a more comprehensive risk evaluation, it is further advised that a healthcare professional accompany BHWs during these visits. Recommendations are further provided for vaccination to scale up health promotion and education efforts. Concerning sanitation profiling, it is suggested that sanitation records be digitized. Moreover, the establishment of a shared drive and investment in digital storage, done in conjunction with the conduct of technical support through workshops on the utilization of Microsoft Excel, is also deemed valuable.
Includes references and appendices.
Written Report (PH 195)
Keywords: Public health -- Philippines -- Magallanes (Cavite).; Health surveys -- Philippines -- Magallanes (Cavite).; Situational analysis (Social sciences) -- Philippines -- Magallanes (Cavite).; Health planning -- Philippines -- Magallanes (Cavite).; Rural health clinics -- Philippines -- Magallanes (Cavite).